EARLY GROWTH OF COFFEE PLANTS AND SOIL FERTILITY PROPERTIES IN RESPONSE TO COFFEE HUSK APPLICATION - Mantovani, José Ricardo; Paula, Deyvid Wilker de; Rezende, Tiago Teruel; Silva, Adriano Bortolotti da; Andrade, Paula Cristina Castro; Landgraf, Paulo Roberto Corrêa (Coffee Science - ISSN 1984-3909, 2018)
Coffee processing generates large amounts of husk, which can be used as organic fertilizer if technical criteria are considered. This study investigated the effect of coffee husk, applied to or incorporated into the soil, on soil fertility properties, early crop growth and nutrient accumulation in coffee plants. The experiment analyzed coffee plants in a greenhouse in pots, in randomized blocks, in a 5x2 factorial arrangement plus a control treatment, with four replicates. The treatments consisted of the combination of five coffee husk rates (3.5; 7; 14; 28, and 56 t ha-1), applied in two forms: spread on the surface or incorporated into the soil, plus the control treatment, without husk application. Portions of 7 dm3 soil were blended with lime, phosphate fertilizer, as well as coffee husk rates in the treatments with residue incorporation, and incubated for 30 days. Thereafter, one coffee seedling per plot was planted, the coffee husk rates were applied on the soil surface for the treatments without residue incorporation, and the plants were left to grow for 180 days. Coffee husk applied to or incorporated into the soil surface increases the K and organic matter contents of the soil, intensifies the early growth of coffee plants and accelerates N and K accumulation in the plant shoots. The application of coffee husk on the surface is more indicated than its incorporation into the soil, and the best rate at coffee planting is equivalent to 20 t ha-1.